2016
DOI: 10.1501/tarimbil_0000001412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead (PB) and cadmium (CD) elements on lipid peroxidation, catalase enzyme activity and catalase gene expression profile in tomato plants

Abstract: Heavy metals are significant abiotic stress factor, affecting various response mechanisms in plants. These responses include: changes in membrane composition, production of small molecules and free radicals, and alterations in the activities of antioxidant enzymes and their gene expressions. For this reason, lipid peroxidation levels (MDA), catalase enzyme activity, and gene expression profiles, quantified by real-time PCR, were analyzed in tomato plants exposed to various concentrations (0, 80, 160, 320, 640 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The expression of cat gene increased in E. aediculatus when exposed to LC50 dose of Cd and Cu after 24 h but started to decrease after 48 h of metal exposure. Similar to this study, earlier reports have mentioned that the expression of cat gene increased in the presence of heavy metal stress in various organisms, but at higher concentrations of heavy metals, decrease in the gene expression has been observed (Aydin et al 2016;Azpilicueta et al 2008;Radhakrishnan 2008;Roh et al 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The expression of cat gene increased in E. aediculatus when exposed to LC50 dose of Cd and Cu after 24 h but started to decrease after 48 h of metal exposure. Similar to this study, earlier reports have mentioned that the expression of cat gene increased in the presence of heavy metal stress in various organisms, but at higher concentrations of heavy metals, decrease in the gene expression has been observed (Aydin et al 2016;Azpilicueta et al 2008;Radhakrishnan 2008;Roh et al 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The concentrations of heavy metals in this study were selected based on the average of reported values of Cd and Pb in agricultural lands. 8,17,18 ZnONPs at 100 mg L −1 has been used in several previous studies without showing any phytotoxic effects on plant seedlings. 7 During the exposure period, the Hoagland solution was avoided due to the high ionic strength of the nutrient solution that induces aggregation of the ZnONPs.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…When the transpiration rate reached 10 mL/day (after 10 days), the plants were transferred from the Hoagland solution to new tubes, which were filled with solutions containing 100 mg L –1 Pb 2+ + 1.0 mg L –1 Cd 2+ and/or 100 mg L –1 ZnONPs in DI water. The concentrations of heavy metals in this study were selected based on the average of reported values of Cd and Pb in agricultural lands. ,, ZnONPs at 100 mg L –1 has been used in several previous studies without showing any phytotoxic effects on plant seedlings . During the exposure period, the Hoagland solution was avoided due to the high ionic strength of the nutrient solution that induces aggregation of the ZnONPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aging of tissues, as well as with a decrease in their viability, the activity of this enzyme naturally decreases. Also, the importance of catalase functioning lies in the adaptation of plants to environmental conditions [ 73 ]. The potato plants used in the experiments were quite young, and when AGr-Cu is added, new environmental conditions are created to which the plant organism needs to adapt.…”
Section: Discussionmentioning
confidence: 99%